Citotoxicidade transdentinária e efeito da carbodiimida (EDC) na biomodificação do colágeno dentinário e na degradação da interface adesiva - Scheffel, Debora Lopes Salles [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The purpose of this study was to evaluate the trandentinal cytotoxicity of carbodiimide (EDC), as well as its influence on dentinal collagen degradation and stability of resin-dentin bonds. In the first experiment, MDPC-23 cells were seeded on the pulp surface of the disks and one of the following solutions was applied on the occlusal surface for 60s: no treatment (negative control), 0.1M, 0.3M or 0.5M EDC; 5% glutaraldehyde (GA); Sorensen buffer or 29% hydrogen peroxide (positive control). Cell viability and morphology were analyzed by MTT, Live/Dead assays, total protein (TP) and collagen production and SEM. Data were analyzed by Kruskal-Wallis and Mann-Whitney tests (p<0.05). Only GA increased cellular metabolism. Cell death by necrosis and cell morphology were not affected by the cross-linker agents. There was no reduction in TP and collagen production after 7 days. For the second experiment, dentin beams were completely demineralized and the variation in elastic modulus (E), MMP activity, dry mass loss, hydroxyproline release (HYP) and collagen thermal degradation (CTD) were analyzed after the dentin treatment for 30s or 60s with the following solutions: water; 0.5M; 1M or 2M EDC and 10% GA. Data from E and MMP activity and HYP release were submitted to Wilcoxon and Kruskal-Wallis or Mann-Whitney tests. Dry mass loss and CTD data were analyzed by ANOVA and Tukey’s tests (p>0.05). GA group obtained the highest E values. All cross-linking agents decreased MMP activity and HYP release and increased CTD. In the third experiment, sixty dentin beams were randomly divided into 6 groups according to the treatment solution: deionized water (control), 0.1M EDC, 0.5M EDC, 0.5M EDC+35% HEMA, 5% proanthocyanidin (PA) or 2% chlorhexidine (CHX). The beams were acid etched and treated for 60s. The total MMP activity was analyzed by a colorimetric assay (Sensolyte®). Data were expressed as absorbance values...

O objetivo geral deste trabalho foi avaliar a citotoxicidade transdentinária da carbodiimida (EDC), bem como sua influência na degradação do colágeno dentinário e na estabilidade da união resina-dentina. No estudo 1, células MDPC- 23 foram plantadas na superfície pulpar de discos de dentina e a superfície oclusal foi tratada por 60s com uma das seguintes soluções: sem tratamento; EDC 0,1M; 0,3M ou 0,5M; glutaraldeído 5% (GA); tampão Sorensen ou H2O2 29%. A viabilidade e a morfologia celular foram analisadas pelos testes de MTT, Live/dead, produção de proteína total (PT), de colágeno e MEV. Os dados foram analisados pelos testes de Kruskal-Wallis e Mann-Whitney (p<0,05). O GA promoveu aumento do metabolismo celular. A morte por necrose e a morfologia celular não foram influenciadas pelos agentes cross-linkers. Não houve redução na produção de PT e colágeno após 7 dias. Para o estudo 2, espécimes de dentina foram completamente desmineralizados e a variação do módulo de elasticidade (E), inibição de MMP, perda de massa, liberação de hidroxiprolina (HYP) e degradação térmica do colágeno (DTC) foram analisados após tratamento com uma das seguintes soluções por 30s ou 60s: água deionizada (controle); EDC 0,5M; EDC 1M; EDC 2M e GA 10%. Os dados referentes ao E, atividade de MMP e liberação de HYP foram submetidos aos testes de Wilcoxon e Kruskal- Wallis ou Mann-Whitney. Os valores de perda de massa e DT foram analisados pelos testes de ANOVA e Tukey (p<0,05). Os melhores resultados quanto ao E foram observados para o GA. Todos os cross-linkers reduziram a atividade de MMP e a liberação de HYP e aumentaram a temperatura de DT do colágeno. No estudo 3, sessenta palitos de dentina foram divididos em 6 grupos de acordo com a solução de tratamento: água deionizada (controle); EDC 0,1M; EDC 0,5M; EDC 0,5M + HEMA 35%; proantocianidina 5% (PA) ou clorexidina (CHX) 2%. Após...
Keywords: Colageno; Dentina; Resistência à tração; Collagen